2006
DOI: 10.1385/abab:133:1:41
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Corn Stover by Low-Liquid Ammonia Recycle Percolation Process

Abstract: A pretreatment method using aqueous ammonia was investigated with the intent of minimizing the liquid throughput. This process uses a flowthrough packed column reactor (or percolation reactor). In comparison to the ammonia recycle percolation (ARP) process developed previously in our laboratory, this process significantly reduces the liquid throughput to one reactor void volume in packed bed (2.0-4.7 mL of liquid/g of corn stover) and, thus, is termed low-liquid ARP (LLARP). In addition to attaining short resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(47 citation statements)
references
References 19 publications
6
38
2
1
Order By: Relevance
“…Untreated SSB exhibited rigid and ordered fibrils with some deposits on the exterior layer (Figure 5a). This outer most layer was observed with different kind of polysaccharides, waxes, lignin, and different binding materials, which tallied with previously reported in corn stover (Kim, Lee, Sunwoo, Kim, 2006), and sorghum leaves and stems (Corredor et al, 2009). In the pretreated SSB, the surface layer was removed and the cell wall was distorted, resulting in exposure of internal structures ( Figure 5b, and 5c) which was consistent with observations of SSB structure by Goshadrou, et al, (2011).…”
Section: Morphological Changessupporting
confidence: 90%
“…Untreated SSB exhibited rigid and ordered fibrils with some deposits on the exterior layer (Figure 5a). This outer most layer was observed with different kind of polysaccharides, waxes, lignin, and different binding materials, which tallied with previously reported in corn stover (Kim, Lee, Sunwoo, Kim, 2006), and sorghum leaves and stems (Corredor et al, 2009). In the pretreated SSB, the surface layer was removed and the cell wall was distorted, resulting in exposure of internal structures ( Figure 5b, and 5c) which was consistent with observations of SSB structure by Goshadrou, et al, (2011).…”
Section: Morphological Changessupporting
confidence: 90%
“…Studies that applied surfactants or protein-based amphiphiles during enzymatic hydrolysis of lignocellulosic biomass with cellulase and/or xylanase, reported that surfactants can increase sugar yield from lignocellulosic substrates [1,19,26,27,37,38,44,45]. In a typical procedure, pretreated biomass is incubated with nonionic surfactants (0.15 to 0.75 g/g glucan) [26,37,38] in a shaking incubator at temperatures of 50-60 °C for 1 h [44], or 15 min-4 h [1,26,36] prior to addition of cellulase.…”
Section: Impact Of Amphiphiles On Hydrolysis and Fermentation Of Biomassmentioning
confidence: 99%
“…A wide range of pretreatment technologies has been developed to enable high saccharification yields at lower enzyme loadings [14,15]. Some of these pretreatments target removal of monomeric sugars [16,17], hemicellulose oligomers [18], lignin and lignin degradation products [19][20][21], while others may also target increased biomass porosity, or a combination of these effects. A more recent approach has been the development of techniques that maintain enzyme secondary structure and solubility, and hence activity for an extended period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural residue, such as corncobs and stovers, is particularly well suited to dilute acid pretreatment [51,73]. A maximum sugar yield of 541.2 mg g−1 wheat stubble was obtained by pretreatment at 2% H2SO4/90 min/121 •C followed by enzyme saccharification.…”
Section: Acidmentioning
confidence: 99%
“…The mechanism is similar to the NaOH pretreatment. When using over lime (0.5g Ca(OH) 2 /g biomass) to pretreated corn stover at 25-55°C, lignin and hemicellulose were selectively uninvolved, so the degree of crystallinity slightly increased from 43% to 60% with delignification, but cellulose was not affected [73]. Both sodium hydroxide and lime have very effective at higher temperatures [79,52].…”
Section: Lime Pretreatmentmentioning
confidence: 99%